Effect of Crumb Rubber as Fine Aggregate Replacement in Cold Mixture Asphalt - Paravita Sri Wulandari; Ken Kertorahardjo; Arianto Thesman; Daniel Tjandra (Institute of Research and Community Outreach - Petra Christian University, 2019)
The number of waste tires has been increasing as an impact of rapidly growing number of vehicles and becomes a global environmental concern. The environmental impact can be reduced by converting the waste tires to crumb rubber and reusing it as a replacement of fine aggregates in asphalt mixture. Dense graded cold mixtures asphalt design was developed for rubberized mixtures with up to 100% (by weight) crumb rubber replacement. Series of laboratory testing were performed for evaluating the Marshall stability and volumetric properties of rubberized cold mixture asphalt. The findings of this laboratory study indicated that Marshall stability and volumetric properties of these mixtures were affected by crumb rubber percentage. Although the use of crumb rubber in cold mixture asphalt could decrease the mechanical and volumetric properties of mixtures, but still has a great potential as a partial fine aggregate replacement in cold mixture asphalt. Rubberized cold mixture asphalt could be considered as a flexible pavement subjected to low traffic medium load.